The IEBM encyclopedia of marketing (London : International Thomson Business Press, 1999)
This book is about: The nature and scope of marketing; The theoretical foundations; Marketing management; The marketing mix; Marketing in practice; ...
Keywords: Marketing; Encyclopedias; Marketing -- Encyclopedias